Perilaku Pencegahan Covid-19 dan Pelatihan Pembuatan Sabun Cuci Tangan Cair (Handsoap) di Rumah Tangga - Yanna Wari Harahap; Suryati Harahap (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Covid-19 is a disease caused by the SARS-CoV-2 virus which is part of the Corona virus type. Efforts to prevent the transmission of Covid-19 by complying health protocols, one of which implementing the behavior of washing hands with soap. Provision of liquid hand washing (handsoap) in households is rarely provided because the price of liquid hand washing soap is higher than others. This has resulted rarely people providing special hand washing soap during this pandemic. There are two types of soap, namely bar soap and liquid soap. The content in liquid soap or bar soap is same. The process of making liquid soap using bar soap can be said to be easy to do. In the manufacturing process, it doesn't require that many materials are used. During the pandemic, we are required to oblige our hands with soap to maintain health. The benefits of washing hands with are to avoid the various of germs. By getting used to using soap, we will maintain health for ourselves and others.